Epigenetic Reprogramming of CD4+ Helper T Cells as a Strategy to Improve Anticancer Immunotherapy - Renaude, Elodie; Kroemer, Marie; Borg, Christophe; Peixoto, Paul; Hervouet, Eric; Loyon, Romain; Adotévi, Olivier (Frontiers in Immunology, 2021)
Evidences highlight the role of various CD4 helper T cells (CD4 Th) subpopulations in orchestrating the immune responses against cancers. Epigenetics takes an important part in the regulation of CD4 Th polarization and plasticity. In this review, we described the epigenetic factors that govern CD4 T cells differentiation and recruitment in the tumor microenvironment and their subsequent involvement in the antitumor immunity. Finally, we discussed how to manipulate tumor reactive CD4 Th responses by epigenetic drugs to improve anticancer immunotherapy.